2012
DOI: 10.1212/wnl.0b013e31823efc42
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lacune subtypes in the Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Objective: Lacunar infarctions are mainly due to 2 microvascular pathologies: lipohyalinosis and microatheroma. Little is known about risk factor differences for these subtypes. We hypothesized that diabetes and glycated hemoglobin (HbA 1 c) would be related preferentially to the lipohyalinotic subtype.Methods: We performed a cross-section analysis of the brain MRI data from 1,827 participants in the Atherosclerosis Risk in Communities study. We divided subcortical lesions Յ20 mm in diameter into those Յ7 mm (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
67
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 31 publications
11
67
1
Order By: Relevance
“…35 During the years, this may cause cerebral hypoperfusion, microinfarctions, and other signs of cerebral small vessel disease. 36 A relationship between BP and lesions in the cerebral whiter matter has been reported, 7,36 especially with midlife hypertension 37,38 and those with poorly controlled hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…35 During the years, this may cause cerebral hypoperfusion, microinfarctions, and other signs of cerebral small vessel disease. 36 A relationship between BP and lesions in the cerebral whiter matter has been reported, 7,36 especially with midlife hypertension 37,38 and those with poorly controlled hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agree with previous cross-sectional data in patients with CADASIL, 10 and active smoking has been reported to also increase the risk of stroke in sporadic SVD. 22 Smoking has multiple effects on the microvasculature, including altered nitric oxide signaling of calcium channels, 23 depletion of the free pool of tissue-type plasminogen activator 24 and enhanced free-radical production. 25 In this study, active smoking was also found to increase the risk of incident dementia independently of other potential risk factors, whereas a previous history of stroke did not change this risk.…”
Section: Discussionmentioning
confidence: 99%
“…12 The false-negative rate is multifactorial and reflects a learning curve in LI CTP pattern identification 2,16,25 but also variability in the size of perfusion abnormality in the context of LI. 15 Traditionally, studies have focused on identifying larger hemispheric perfusion defects with or without concurrent deep abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…These results mirror a large community-based prospective cohort study of 15,792 middle-aged adults in whom both hypertension and diabetes were associated with smaller (but not large) infarcts. 25 The utility of CTP in the context of LI has been previously studied. 8,13,14 Early clinical deterioration occurs in 27%-62% of LI cases and is not reliably predicted clinically.…”
Section: Discussionmentioning
confidence: 99%